Improving Students’ Vocabulary Mastery through the Song “Let It Go” in the Seventh Grade of SMP PAB 2 Helvetia - Cindy Elsa Mayuri; Yenita Uswar (Edumaspul: Jurnal Pendidikan, 2025)
This study was conducted to find out how the use of the song "Let It Go" can improve the English vocabulary mastery of seventh grade students of SMP PAB 2 Helvetia.The problem revolves around the students’ low mastery of the English language which resulted from boring teaching methods and students’ disinterest in learning. This study was conducted in the form of Classroom Action Research (CAR) with two cycles. Each cycle consists of planning, implementation, and observation, and reflection. For the collection of data, several techniques were used: vocabulary tests (pre-test, post-test cycle I, post-test cycle II), observation, interviews, and documentation. Given the results, students seemed to master the vocabulary quite well. Before the pre-test for cycle I, students achieved an average score of 61.25. Scores improved to 78.33 in the post-test for cycle I, then to 92.27 in the post-test for cycle II. The average score of students showing improvement also increased. In the pre-test, learning completeness scores increased from 33.33% in cycle I to 75% during cycle II, and to 94.44%. The results of this study exemplify the "Let It Go" approach and its effectiveness in helping students master vocabulary. Lessons were designed to provide an enjoyable learning environment, and students were motivated to understand the meanings of words in the songs and the contextual relevance of the lyrics.